Scientometric Analysis of Medical and Non-Medical Highly Cited Papers of Iran in Essential Science Indicator (ESI) - Haseli mofrad, Azade; Shekofteh, Maryam; Kazerani, Maryam (Archives of Advances in Biosciences, 2017)
The aim of the present research is to study scientometric indicators (the number of articles and citations, the mean citation per paper, H-index, Y-index, and the national and international collaboration) of medical and non-medical highly cited papers of Iran in the Essential Science Indicators (ESI). The research population is all highly cited articles of Iran in ESI during 2005 to 2015. Data was retrieved from ESI and was analyzed using descriptive statistics. Findings show that Iran has achieved the 35th global rank in terms of the number of highly cited articles. This rank encompasses % 0.1 of the highly cited medical subject areas and % 0.6 of the global portion in non-medical areas. The growth of highly cited papers in non-medical subject areas is more than medical subject ones. Y-index indicates that the role of authors in most highly cited articles in both medical and non-medical subject areas is either as the corresponding or the first author, with an inclination towards the first author. Most of Iran’s highly cited articles in the medical subject areas are based on international collaborations, but in the non-medical areas, they are based on national collaborations. The most international collaborations are with U.S, Canada and England, respectively. H-index of Iran is 141. As a whole, in quantitative and qualitative assessment, non-medical subject areas have a better status than medical subject areas. In general, it can be said that the status of scientific products and the international status of Iran is not satisfactory. Professional planning and policy should be taken into consideration by Iran.